Anorectal gastrointestinal stromal tumor: a rare case report - Shanmugam, Subbiah; Singodiya, Suyash (International Surgery Journal, 2024)
A gastrointestinal stromal tumor (GIST) is a mesenchymal tumor of gastrointestinal tract arising from the interstitial cell of Cajal with rare occurrence in anorectum. Mutations of c-KIT proto-oncogene characterized by the expression of the KIT (CD-117) tyrosine kinase or platelet-derived growth factor receptor alpha (PDGFRα) is frequently seen with these tumours. Elderly patients with age greater than 50 are at higher risk of GIST. Here, we present a case of a 51-year-old male who presented with vague dull aching pain in the right-side perianal area since last one month with a submucosal mass in the right posterolateral wall of the anal canal and rectum. The histopathological and immunohistochemistry study of the biopsy sample reported strongly positive for CD117 and less than 3% of tumor cells showed Ki67 positivity. The patient underwent laparoscopic abdomino-perinel resection. Post-operatively, the patient was started on adjuvant imatinib with regular follow-up.